PELAKSANAAN PENILAIAN AUTENTIK PADA MATA PELAJARAN EKONOMI DI SMA NEGERI SE-KABUPATEN OGAN ILIR - Melinda Niza Pransisca; Riswan Jaenudin; Dewi Koryati (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
This research discusses the implementation of authentic assessment in the subjects Economics in SMAN se-Ogan Ilir. The research problems "How is the implementation of authentic assessment in the subjects Economics in SMAN se-Ogan Ilir seen through aspects of assessment planning, implementation assessment, processing and reporting of assessment and assessment instruments and techniques used?". The research method used descriptive method. Subjects consisted of two teachers of Economics in SMAN 1 Indralaya and 2 Economics teacher at SMAN 2 Tanjung Raja. Data were collected through observation, interviews, and documentation. Each data is analyzed using a percentage formula. The results of the research aspects of the planning assessment indicates the category of the good, the implementation aspect ratings also indicate the category of the good, aspects of processing and reporting of assessment identifies the categories very good, so it can be concluded that the implementation of authentic assessment in the subjects Economics in SMAN se-Ogan Ilir included in both categories. Schools should create an authentic assessment in a simple way so that teachers are not too bothered by the scoring system. For further research, is expected to examine the forms of matter in accordance with the characteristics of authentic assessment, and is expected to examine the effectiveness of the assessment format issued by Kemendikbud in guide books for high school assessment used by teachers.